(untitled) (Proceedings of International Conference on Special Education, 2019)
Project-based learning is a learning that provides direct learning experience to students through scientific inquiry activities carried out by independent students (student-directed scoring inquiry) with the support of technology and collaboration to solve real problems in daily life (real world problems) (Krajcik et al., 1999. This study uses a systematic literature review. A systematic literature review is a series of studies using the internet, then synthesized on a particular topic. The literature used in this study is previous research on a national scale. Research in the form of articles during 2013-2017. Project-based learning can improve students’ understanding of the material, especially those related to skills. In addition, active students, directly involved in making projects, make plans to obtain results, improve the ability of students with visual impairments, and improve the independence of blind students.